2011
DOI: 10.1177/1934578x1100600129
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition of Essential Oil of Senecio coincyi, an Endemic Species of the Central Iberian Peninsula

Abstract: The essential oil has been studied of leaves of Senecio coincyi Rouy, an endemic species of Spain restricted to a very small area of the Central Iberian Peninsula. Samples from five locations were obtained by hydrodistillation and extraction and analysed by gas chromatography-mass spectrometry. The main compound was 1-tridecene (28.1 ± 8.5%). The presence of unsaturated hydrocarbons (1-undecene, 1-dodecene and 1-tridecene) seems to indicate a chemotaxonomic relationship between Senecio coincyi and S. congestus. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The compound 1-Dodecene is plant volatile compound which has been previously detected using GC-MS in S. incanum,Oryza sativa¸ Ipomoea separia, Seneciocoincyi, S. congestus among other plants [41][42][43]. This compound has been reported to have antimicrobial and antioxidant activity as well as used in manufacture of detergents [44,42].…”
Section: Gc-ms Results Of Solanum Incanummentioning
confidence: 99%
“…The compound 1-Dodecene is plant volatile compound which has been previously detected using GC-MS in S. incanum,Oryza sativa¸ Ipomoea separia, Seneciocoincyi, S. congestus among other plants [41][42][43]. This compound has been reported to have antimicrobial and antioxidant activity as well as used in manufacture of detergents [44,42].…”
Section: Gc-ms Results Of Solanum Incanummentioning
confidence: 99%
“…The flowers of S. coincyi are pollinated by several insect species. Arrabal et al (2011) found that the main compound of the essential oil of S. coincyi leaves is 1-tridecene. This compound is known to be secreted by several insect groups (Coleoptera, Hymenoptera) and has pheromone properties.…”
Section: Discussionmentioning
confidence: 99%